"Creatively in Coalition" from Palestine to India: Weaving stories of refusal and community as decolonial praxis. (14th June 2021) - Atallah, Devin G.; Dutta, Urmitapa
Abstract: Colonialism and coloniality constitute the backbone of modernity. Colonial structures/systems are predicated on recurring patterns of domination and violence. Decolonial movements are rehumanizing and abolitionist projects guided by Global South peoples' reimagining and reclaiming of what it means to be human. Decolonial praxes therefore require transnational efforts to decenter Whitestream academic institutions as hubs of knowledge production. In light of this, we question the boundaries of what we consider to be research in psychology as we walk in the legacies of struggle and survival—of our grandmothers and grandfathers, and so many ancestors who never used the word "decolonial". Weaving together stories of refusal and community grounded on our work in Palestine and India, we demonstrate how our decolonial strivings require us to continuously rediscover ways of being present, being in struggle, and being human together as we work ''creatively in coalition'' with our communities. Through our stories of accompaniment, and bringing them into conversation with each other, we disrupt violent, colonially‐configured borders. In our world‐making coalitions and the writing of this article, we turn to a praxis that allows for the revisioning of justice as irresistible and interlinked, ungovernable and in defiance of borders and walls.